Особливості стратегії творчості Ю. Яновського - Гмиря, Т. П.; Шарова, Тетяна Михайлівна; Шарова, Татьяна Михайловна; Sharova, Tetiana (My University, 2021)
UK: У статті розглядаються питання особливостей творчої манери Ю. Яновського. Акцентується увага на тому, що Ю. Яновському вдалося створити індивідуально-авторський дискурс, котрий виражає сутнісний зв’язок із універсальними засновками людської екзистенції, з вічними буттєвими істинами. EN: The article considers the peculiarities of the creative style of Yu. Yanovsky. Emphasis is placed on the fact that Yu. Yanovsky managed to create an individual-authorial discourse, which expresses the essential connection with the universal foundations of human existence, with eternal existential truths.
Peculiarities of the Creativity strategy of Yu. Yanovsky
Keywords: особливості творчості; стратегія розвитку; література; психлогізм,; проза; поезія; features of creativity; development strategy; literature; psychologism; prose; poetry